Association of hyperkalemia with clinical outcomes in advanced chronic kidney disease - Fernando Caravaca-Fontán; Julián Valladares; Rosa Díaz-Campillejo; Sergio Barroso; Enrique Luna; Francisco Caravaca (Nefrología (English Edition), 2019)
Introduction: Patients with advanced chronic kidney disease (CKD) are at greatest risk of hyperkalemia (HK). The relationship between HK and negative outcomes (mortality or progression of renal insufficiency) in non-dialysis dependent CKD patients is controversial. Aims: To determine the incidence, prevalence, and factors related with HK in a cohort of CKD patients, and its relationship with mortality, hospitalization rate, CKD progression, and dialysis initiation. Material and methods: A retrospective, observational study in an incident cohort of adult patients with stage 4 or 5 CKD not on dialysis. Inclusion criteria were: having at least three consecutive estimated glomerular filtration rate (eGFR) measurements in a follow-up period >3 months. Decline in renal function was estimated as the slope of the individual linear regression line of eGFR over follow-up time. HK was defined as serum K levels ≥5.5 meq/l. Associations of HK with outcomes were adjusted for major confounding variables in the multivariate analysis. Results: The study group consisted of 1079 patients (574 males, mean age: 65 ± 14 years) with mean baseline eGFR 14.8 ± 4.5 ml/min/1.73 m2. Mean follow-up time was 15 months with a median of 7 serum sample determinations per patient. HK was observed at baseline in 26% of patients; in at least one serum sample during the individual follow-up period in 68%; or chronically (>50% of samples) in 33% of patients. By multivariate logistic regression, the best determinants of chronic HK were: male sex (OR = 1.529; 95% CI [1.154–2.025], p = .003), serum bicarbonate (OR = 0.863 [0.829–0.900], p < .0001), diuretic treatment (OR = 0.743 [0.556–0.992], p = .044), and angiotensin converting enzyme inhibitor and/or angiotensin receptor blockers (OR = 4.412 [2.915–6.678], p < .0001). Patients whose serum K levels were in the upper quartile showed a significantly faster CKD progression (−4.05 ± 5.22 vs. −2.69 ± 5.61 ml/min/1.73 m2/year, p < .0001), and more frequent dialysis initiation (63% vs. 57%, p = .115), though lower mortality (9% vs. 17%, p = .003) and hospitalization rates (2.68 ± 5.94 vs. 3.16 ± 6.77 days per year, p = .301) than the other study patients. However, in the multivariate analysis, average serum K levels were not independently associated with the clinical outcomes investigated. Conclusion: HK is a common biochemical finding in non-dialysis dependent CKD patients, mainly associated with prescribed medication. However, HK was not independently associated with major negative clinical outcomes. Resumen: Introducción: Los pacientes con enfermedad renal crónica (ERC) tienen un alto riesgo de desarrollo de hiperkaliemia (HK). La relación entre HK y una mala evolución (mortalidad o progresión de la insuficiencia renal) en la ERC avanzada es controvertida. Objetivos: Determinar la incidencia, prevalencia, y factores relacionados con la HK en una cohorte de pacientes con ERC, y su relación con la mortalidad, tasa de hospitalización, progresión de la ERC, y necesidad de inicio de diálisis. Material y métodos: Estudio retrospectivo de observación en una cohorte de pacientes adultos con ERC estadio 4–5. Los criterios de inclusión fueron: tener al menos 3 medidas consecutivas de filtrado glomerular (FG) durante un periodo superior a 3 meses. HK se definió como un K sérico ≥ 5,5 mmol/l. La asociación entre HK y las variables de evolución fue ajustada a los principales factores de confusión mediante análisis mutivariantes. Resultados: Se incluyeron 1079 pacientes (574 hombres, edad media: 65 ± 14 años) con un FG basal 14,8 ± 4,5 ml/min/1,73 m2. El tiempo medio de seguimiento fue de 15 meses y se determinaron una mediana de 7 muestras por paciente. Basalmente un 26% de pacientes tenía HK, un 68% en al menos una muestra durante el periodo individual de seguimiento, y un 33% de forma crónica (HK > 50% del seguimiento individual). Mediante regresión logística multivariable los mejores determinantes de la HK fueron: sexo masculino (OR = 1,529; IC 95% [1,154-2,025], p = 0,003), bicarbonato sérico (OR = 0,863, [0,829-0,900], p < 0,0001), tratamiento diurético (OR = 0,743, [0,556-0,992], p = 0,044), y tratamiento con inhibidores del sistema renina-angiotensina (OR = 4,412, [2,915-6,678], p < 0,0001). Estos pacientes con HK mostraron una progresión de la ERC significativamente más acelerada (−4,05 ± 5,22 vs. −2,69 ± 5,61 ml/min/1,73 m2/año, p < 0,0001), e inicio más frecuente de diálisis (63% vs. 57%, p = 0,115), pero menos mortalidad (9% vs. 17%, p = 0,003), y tasa de hospitalización (2,68 ± 5,94 vs. 3,16 ± 6,77 días/año, p = 0,301) que el resto de los pacientes estudiados. Sin embargo en el análisis multivariante, HK no se asoció de forma independiente con ninguna de las variables de evolución investigadas. Conclusión: HK es un hallazgo bioquímico muy frecuente en la ERC avanzada, que se asocia con algunos medicamentos de uso habitual. Sin embargo, HK no se asocia de forma independiente con ninguna de las variables de mala evolución clínica estudiadas. Keywords: Chronic kidney disease, Hyperkalemia, Mortality, Palabras clave: Enfermedad renal crónica, Hiperkaliemia, Mortalidad